Comparative genomics reveals diversified CRISPR-Cas systems of globally distributed Microcystis aeruginosa, a freshwater bloom-forming cyanobacterium - Yang, Chen; Lin, Feibi; Li, Qi; Li, Tao; Zhao, Jindong (Frontiers in Microbiology, 2015)
Microcystis aeruginosa is one of the most common and dominant bloom-forming cyanobacteria in freshwater lakes around the world. Microcystis cells can produce toxic secondary metabolites, such as microcystins, which are harmful to human health. Two M. aeruginosa strains were isolated from two highly eutrophic lakes in China and their genomes were sequenced. Comparative genomic analysis was performed with the 12 other available M. aeruginosa genomes and closely related unicellular cyanobacterium. Each genome of M. aeruginosa containing at least one clustered regularly interspaced short palindromic repeat (CRISPR) locus and total 71 loci were identified, suggesting it is ubiquitous in M. aeruginosa genomes. In addition to the previously reported subtype I-D cas gene sets, three CAS subtypes I-A, III-A and III-B were identified and characterized in this study. Seven types of CRISPR direct repeat have close association with CAS subtype, confirming that different and specific secondary structures of CRISPR repeats are important for the recognition, binding and process of corresponding cas gene sets. Homology search of the CRISPR spacer sequences provides a history of not only resistance to bacteriophages and plasmids known to be associated with M. aeruginosa, but also the ability to target much more exogenous genetic material in the natural environment. These adaptive and heritable defense mechanisms play a vital role in keeping genomic stability and self-maintenance by restriction of horizontal gene transfer. Maintaining genomic stability and modulating genomic plasticity are both important evolutionary strategies for M. aeruginosa in adaptation and survival in various habitats.